Nilai-Nilai Komunikasi Islam Dalam Falsafah Hidup Masyarakat Lampung - Abimanyu Satrio Prakoso (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Communication is an activity which is not far from the joints of the life of the Lampung community, which is now a social tool in the association, Lampung society is a heterogeneous society consisting of various religious diversity, ethnicity, ethnicity, language, customs and so on. Communication is done to meet the needs of life, individuals, and groups interacting both ethnicity and with other individuals or groups with different cultural backgrounds, in an era when communication becomes a stumbling block among the community, where differences in ethnicity and language become a problem, whereas Lampung society itself has a moral order (Piilpesenggiri), pienggpesenggiri is a philosophy of life of Lampung society's view of life or life guidelines. This study aims to explain the meaning of the philosophy of life of the Lampung community to the values ​​of Islamic communication, related to how the pesenggiripiil is processed as communication values ​​and communication strategies in the social community of Lampung. PiilPesenggiri has become alienated from the daily lives of Lampung people. This study found the fact that the various values ​​of PiilPesenggiri's philosophy of life were philosophically coherent with the values ​​of communication.